2014
DOI: 10.1007/s00339-014-8255-0
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of ablation threshold and LIPSS formation on copper thin films by accumulative UV picosecond laser shots

Abstract: International audienceThe ablation threshold and Laser-induced periodic surface structure (LIPSS) formation on copper thin film were investigated using a picosecond laser (Nd:YAG laser: 266 nm, 42 ps, 10 Hz). We show that the ablation threshold varies with respect to the number of laser shots (N) on two different substrates. The single-shot ablation threshold was estimated to be close to 170 ± 20 mJ/cm2. The incubation coefficient was estimated to be 0.68 ± 0.03 for copper thin films on silicon and glass subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 32 publications
3
18
0
Order By: Relevance
“…The period of the observed structures is much smaller that the laser beam wavelength (from 265 to 500 nm, against 790 nm for the beam wavelength). Such a small period has already been reported in the literature [31,32] for metal surfaces Dark periodic circular areas (diameter of about 15 µm) appear on this micrograph and correspond to the laser spots but no visible craters were produced after a single laser pulse. No laser scanning was carried out here, a single area was irradiated.…”
Section: Mea Preparation and Fuel Cell Characterizationssupporting
confidence: 81%
“…The period of the observed structures is much smaller that the laser beam wavelength (from 265 to 500 nm, against 790 nm for the beam wavelength). Such a small period has already been reported in the literature [31,32] for metal surfaces Dark periodic circular areas (diameter of about 15 µm) appear on this micrograph and correspond to the laser spots but no visible craters were produced after a single laser pulse. No laser scanning was carried out here, a single area was irradiated.…”
Section: Mea Preparation and Fuel Cell Characterizationssupporting
confidence: 81%
“…It was confirmed that the electron-phonon coupling constant is directly related the electron and lattice temperatures, and these temperatures in turn depend on the fluence incident on the target surface. The input laser fluence should be more than the ablation threshold fluence that could melt the sample surface to generate periodic structures and the earlier reported ablation threshold fluence for Cu was 1.7±0.2 J/cm 2 [40]. Following some of the previous reports we understand that the shape of the periodic surface structures change with respect to laser fluence and number of pulses.…”
Section: Effects Of Pulse Energy On Cu Nss In Acn Prepared By Ps Pulssupporting
confidence: 62%
“…A calculation by Equation ( 9 ) yields the accumulation coefficient S = 0.70 ± 0.01. The literature values for the accumulation coefficient are: S = 0.77 (1064 nm, 10 ps, 50 kHz) 42 ; S = 0.79 (1064 nm, 10 ps, 50 kHz) 33 ; S = 0.68 (266 nm, 42 ps, 10 Hz) 59 ; S = 0.75 (800 nm, 30 fs, 1 kHz) 60 . The accumulation coefficient measured in our work coincides well with the results from other groups.…”
Section: Methodsmentioning
confidence: 99%